Construção de um susceptômetro AC e a susceptibilidade magnética de microfios amorfos recobertos por vidro - Gomes, Rafael Cabreira (2010)
Glass covered microwires are materials with soft magnetic properties suitable to several technological applications, specially in magnetic sensors. The main feature of these wires, with negative magnetostriction, it is the magnetic domain structure, which are studied in several research centers. In this work it was developed an AC susceptometer capable to operate at room temperature at different applied fields and stress and another one to operate in cryogenic temperatures. The AC susceptibility technique carry out information either about the dynamic magnetic processes as the dissipative one that occur into the samples. In particular, microwires samples with nominal composition of Co68.25Fe4.25Si12.5B15 were studied. These Co-rich microwires exhibit the bamboo-like domain structure, meaning an axially magnetized core surrounded by a circumferentially magnetized shell. The AC susceptibility study on these samples give us information as, for example, that with the increase of the applies stress, there is an increase of the volume of the circumferentially magnetized shell at expenses of the inner core volume. It was also verified that, the magnetic behavior with the reduction of the temperature is similar to that observed when the microwires are axially stressed. This fact is due to the competition between the maganetoelastic and magnetostatic energies.